WAYS TO LEARN AND FACILITATE THE DIFFICULTIES IN THE PROCESS OF WORKING WITH LISTS ON THE DATA STRUCTURE AND ALGORITHMS MODULE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is written about the relief of working with programs in the educational process, that is, in order to increase the knowledge of the students and learners. Using programming, it is important to use the data structure and theirs algorithms, implementing it, obtaining results in practice. The use of lists in the Dynamic Data Structure in different views is also mentioned separately.